The Reflection of Social Stratification in Titanic - Sunra, La; Junaid, Syahruni (State University of Makassar, 2022)
This article aimed at analyzing the reflection of social stratification in a twentieth-century-spectacular movie, TITANIC. The study used descriptive method, and the data were analyzed using genetic structuralism approach which is essentially the combination between intrinsic approach and extrinsic one. The analysis showed that in social life, the members of society were divided into some classes (high and lower classes). This classification differentiated the degree of life of human being and surely affected the condition of people's life: the way they acted, the way they talked, the way they treated and viewed others, and even in love. A high class girl, Rose DeWitt Bukater, met with a third class passenger, Jack Dawson. They were in love, but because they came from different family background, they had to face challenges which prohibited them to be together, especially from Rose's family. They never gave up until they were finally separated by destiny. Jack became one of the victims who died in the great disaster when the ship sank.Keywords: Reflection, social Stratification